African and international financial markets interdependencies: Does Covid-19 media coverage make any difference? - Godfred Amewu; Mohammed Armah; Saint Kuttu; Baah Aye Kusi (Research in Globalization)
This study examines the co-movement and time-varying integration between equity, exchange rate, and international market volatility indices across different time–frequency domains using - bi-partial wavelet, - supplemented by dynamic conditional correlation-generalised autoregressive conditional heteroskedasticity (DCC-GARCH), - and BEKK GARCH model for selected African countries. First, the findings indicate that the co-movement between equity and exchange rates during the pandemic was exacerbated by global COVID-19 media coverage. The findings indicate that there has been a substantial risk transfer between exchange rates and stock returns during the COVID-19 pandemic, resulting in a decline in domestic stock returns and subsequent capital outflows, which in turn increased the exchange rate. Given the growing difficulties in diversification, specific information on the volatility of financial market connectedness is required to plan hedging strategies. To explore the influence of global market volatility on Africa’s equity and currency markets, it is crucial to analyse the relationship between regional and global market fluctuations, especially given the negative impact of the COVID-19 pandemic. Our empirical research demonstrates that the VIX and OVXCL indices play a significant role in transmitting spillovers to currency and equity markets in Africa. This suggests that the sentiment indicators provided by the VIX and OVXCL can be useful in predicting the behaviour of Africa’s currency and equity markets.